Using Speech to Reply to SMS Messages While Driving: An In-Car Simulator User Study - Ju, Yun-Cheng; Paek, Tim; Ju, Y. C. (Association for Computational Linguistics, 2010)
Speech recognition affords automobile drivers a hands-free, eyes-free method of replying to Short Message Service (SMS) text messages. Although a voice search approach based on template matching has been shown to be more robust to the challenging acoustic environment of automobiles than using dictation, users may have difficulties verifying whether SMS response templates match their intended meaning, especially while driving. Using a high-fidelity driving simulator, we compared dictation for SMS replies versus voice search in increasingly difficult driving conditions. Although the two approaches did not differ in terms of driving performance measures, users made about six times more errors on average using dictation than voice search.